REKONSTRUKSI TEORI SELF-DISCLOSURE DALAM KONSELING ISLAM ERA MEDIA SOSIAL - Rifqi Fauzi; Arief Rachman; Asriyanti Rosmalina (Program Studi Komunikasi dan Penyiaran Islam, Fakultas Dakwah dan Komunikasi, Universitas Islam Bunga Bangsa Cirebon, 2025)
This study examines the reconstruction of self-disclosure theory in the context of Islamic counseling in the era of social media that increasingly dominates contemporary human communication patterns. The development of digital platforms has fundamentally changed the way individuals reveal themselves, including in counselor-client relationships based on Islamic values. This study aims to analyze the relevance of classical self-disclosure theory according to Western psychology perspectives with the principles of self-disclosure in Islamic teachings, and to reconstruct a new integrative and contextual conceptual framework in accordance with the challenges of the social media era. The methodology used is a systematic literature review with a content analysis approach to relevant primary and secondary sources, covering Islamic counseling literature, communication psychology, and social media studies. The results show that self-disclosure theory needs to be reconstructed by incorporating the dimensions of amanah, digital mahram, and internet ethics as core components in social media-based Islamic counseling practice. This reconstruction produces an integrative model called the Islamic Self-Disclosure Model (MSDI) that holistically considers aspects of spirituality, Islamic ethics, and digital literacy. These findings contribute to the development of Islamic counseling practices that are adaptive to technological changes without abandoning the foundation of sharia values.